Franny and Zooey - Salinger, J. D. (Jerome David), 1919-2010. (Boston : Little, Brown and Company, 1991)
Franny, dissatisfied with everything, has a disastrous date with her boyfriend Lane. When she returns home, her older brother helps her solve her problem.
Wilson's Fiction.
Wilson's Senior High School.
Wilson's Fiction, January 1996.
Wilson's Senior High School, November 1997.
Adult
Keywords: Brothers and sisters -- Fiction; Dating (Social customs) -- Fiction; Dating (Social customs) -- Fiction; Siblings -- Fiction